2017
DOI: 10.1177/1073191117715729
|View full text |Cite
|
Sign up to set email alerts
|

Item Response Theory Analysis of the Psychopathic Personality Inventory–Revised

Abstract: This study examined item and scale functioning in the Psychopathic Personality Inventory-Revised (PPI-R) using an item response theory analysis. PPI-R protocols from 1,052 college student participants (348 male, 704 female) were analyzed. Analyses were conducted on the 131 self-report items comprising the PPI-R's eight content scales, using a graded response model. Scales collected a majority of their information about respondents possessing higher than average levels of the traits being measured. Each scale c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 50 publications
(74 reference statements)
3
12
0
1
Order By: Relevance
“…For example, the reverse-scored items on the Social Interaction Anxiety Scale (Mattick & Clarke, 1998) assess extroversion and are not specific to social anxiety (Rodebaugh et al, 2007). Eichenbaum et al (2019) compared the functioning of the reverse-scored items to the directly scored items on the PPI-R. They found a clear pattern in which most of the poorest performing items (lowest a parameters) were keyed in the opposite direction from the majority of the items on a subscale.…”
Section: Reverse Scoringmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the reverse-scored items on the Social Interaction Anxiety Scale (Mattick & Clarke, 1998) assess extroversion and are not specific to social anxiety (Rodebaugh et al, 2007). Eichenbaum et al (2019) compared the functioning of the reverse-scored items to the directly scored items on the PPI-R. They found a clear pattern in which most of the poorest performing items (lowest a parameters) were keyed in the opposite direction from the majority of the items on a subscale.…”
Section: Reverse Scoringmentioning
confidence: 99%
“…threshold parameters are estimated for each step in the item (e.g., b i1 , b i2 , and b i3; Penfield, 2014). The GRM has been applied to a number of psychopathy measures, including the PPI-R (Eichenbaum et al, 2019). Model fit was assessed by calculating chi-square statistics for each item, such that a significant value indicates poor model fit.…”
Section: Graded Response Irt Model and Model Fitmentioning
confidence: 99%
See 1 more Smart Citation
“…The implementation of polytomous item response theory (IRT) models to inform instrument design and validation has been increasing across social and educational contexts where rating scales are usually used (e.g., Carle et al, 2009;Sharkness and DeAngelo, 2011;Cordier et al, 2019;French and Vo, 2020). Examples include the use of polytomous IRT to develop parallel and short forms of existing measures (e.g., Uttaro and Lehman, 1999) and to detect items that show different item functioning (DIF; e.g., Eichenbaum, et al, 2019;French and Vo, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Studies also regularly reported sex factorial invariance of the main instruments dedicated to assess psychopathic traits (Anestis et al, 2011; Drislane & Patrick, 2017; Warren et al, 2003). Regarding differences in item functioning, specific analyses have found that men more readily endorsed and were better discriminated by criteria assessing affective components of psychopathy (Bolt, Hare, Vitale, & Newman, 2004; Eichenbaum, 2019; Gummelt, Anestis, & Carbonell, 2012). More specifically, affective items seem to outperform interpersonal items for discriminating psychopathy in men, whereas interpersonal items would outperform affective items in women (Schrum & Salekin, 2006).…”
mentioning
confidence: 99%